2016
DOI: 10.1530/erc-16-0181
|View full text |Cite
|
Sign up to set email alerts
|

PVALB diminishes [Ca2+] and alters mitochondrial features in follicular thyroid carcinoma cells through AKT/GSK3β pathway

Abstract: We have identified previously a panel of markers (C1orf24, ITM1 and PVALB) that can help to discriminate benign from malignant thyroid lesions. C1orf24 and ITM1 are specifically helpful for detecting a wide range of thyroid carcinomas, and PVALB is particularly valuable for detecting the benign Hürthle cell adenoma. Although these markers may ultimately help patient care, the current understanding of their biological functions remains largely unknown. In this article, we investigated whether PVALB is critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…In our study, the expression of PVALB was slightly higher in cases with suboptimal surgical resection. In contrast, PVALB expression has been reported to be higher in benign vs malignant thyroid lesions and in normal glial cells vs glioma [36,37].…”
Section: Discussionmentioning
confidence: 91%
“…In our study, the expression of PVALB was slightly higher in cases with suboptimal surgical resection. In contrast, PVALB expression has been reported to be higher in benign vs malignant thyroid lesions and in normal glial cells vs glioma [36,37].…”
Section: Discussionmentioning
confidence: 91%
“…PCCL3 cells with ectopic expression of FAM129A and control (empty vector) were fixed and stained as previously described (Mendes et al 2016). Cells were fixed in Karnovisky buffer (4% paraformaldehyde and 2% glutaraldehyde in 0.05 M sodium cacodylate buffer, pH 7.2) (Sigma-Aldrich).…”
Section: Monitoring Autophagosomes Formation By Transmission Electronmentioning
confidence: 99%
“…The TDRD12 and LIN28A together with TDRKH which also was upregulated in PTM/PM but downregulated in TM/PTM were enriched into 1 MF, GO:0050731∼positive regulation of peptidyl-tyrosine phosphorylation. Another one, PVALB, went on being upregulated at subsequent process, indicating its importance during the cancerization (Mendes et al, 2016;Zhong et al, 2018). The results demonstrated that those DEGs might have different physiological significance in the transitions from the PM to the PTM and from the PTM to the TM in biogenesis of a secondary tumor.…”
Section: Discussionmentioning
confidence: 88%